Protection From Natural Immunity Against Enteric Infections and Etiology-Specific Diarrhea in a Longitudinal Birth Cohort. (27th January 2020) - Rogawski McQuade, Elizabeth T; Liu, Jie; Kang, Gagandeep; Kosek, Margaret N; Lima, Aldo A M; Bessong, Pascal O; Samie, Amidou; Haque, Rashidul; Mduma, Estomih R; Shrestha, Sanjaya; Leite, Jose Paulo; Bodhidatta, Ladaporn; et al.
Abstract: Background: The degree of protection conferred by natural immunity is unknown for many enteropathogens, but it is important to support the development of enteric vaccines. Methods: We used the Andersen-Gill extension of the Cox model to estimate the effects of previous infections on the incidence of subsequent subclinical infections and diarrhea in children under 2 using quantitative molecular diagnostics in the MAL-ED cohort. We used cross-pathogen negative control associations to correct bias due to confounding by unmeasured heterogeneity of exposure and susceptibility. Results: Prior rotavirus infection was associated with a 50% lower hazard (calibrated hazard ratio [cHR], 0.50; 95% confidence interval [CI], 0.41–0.62) of subsequent rotavirus diarrhea. Strong protection was evident against Cryptosporidium diarrhea (cHR, 0.32; 95% CI, 0.20–0.51). There was also protection due to prior infections for norovirus GII (cHR against diarrhea, 0.67; 95% CI, 0.49–0.91), astrovirus (cHR, 0.62; 95% CI, 0.48–0.81), and Shigella (cHR, 0.79; 95% CI, 0.65–0.95). Minimal protection was observed for other bacteria, adenovirus 40/41, and sapovirus. Conclusions: Natural immunity was generally stronger for the enteric viruses than bacteria, potentially due to less antigenic diversity. Vaccines against major causes of diarrhea may be feasible but likely need to be more immunogenic than natural infection. Abstract : We estimated natural immunity to enteric pathogens as the effects of previous infections on the incidence of subsequent infections in children under 2. Prior rotavirus, Cryptosporidium, norovirus GII, astrovirus, and Shigella infections were associated with lower risk of subsequent diarrhea.